Improving Fitness Levels of Teenagers Online Game Addicts with High Intensity Interval Training - Aniek Puspitosari; Rini Yuniarti (Journal of Health, 2025)
Teenagers addicted to online games tend to have low fitness levels. The most effective exercise to increase fitness levels is High-Intensity Interval Training (HIIT) because it is carried out in a short time, is flexible, and causes less injury to the musculoskeletal system. HIIT is a cardiorespiratory exercise that uses aerobic principles to increase fitness levels, especially at the maximum volume of oxygen (VO2max). This study aims to determine the effect of High-Intensity Interval Training on the fitness level of teenagers who are addicted to online games. This research is quantitative research that uses the Pre-Experimental Design type one group pretest-posttest. The sampling technique used is purposive sampling with the number of respondents as many as 25 people. The instrumen used in this research is the Harvard step test. The High-Intensity Interval Training intervention was conducted in 8 sessions for 4 weeks. The data analysis method used is the paired samples t-test. Research respondents based on age were dominated by the late adolescent category (52%), based on the BMI classification dominated by the normal category (60%). The results of the paired samples t-test test obtained sig. 0.000 which means the value of sig. <0.05, it can be concluded that the High-Intensity Interval Training (HIIT) intervention has an effect on the fitness level of teenagers who are addicted to online games.